Air‐Stable Protective Layers for Lithium Anode Achieving Safe Lithium Metal Batteries. Issue 1 (18th December 2022) - Li, Runjing; Fan, Yining; Zhao, Chuan; Hu, Anjun; Zhou, Bo; He, Miao; Chen, Jiahao; Yan, Zhongfu; Pan, Yu; Long, Jianping
Abstract: With markedly expansive demand in energy storage devices, rechargeable batteries will concentrate on achieving the high energy density and adequate security, especially under harsh operating conditions. Considering the high capacity (3860 mA h g −1 ) and low electrochemical potential (−3.04 V vs the standard hydrogen electrode), lithium metal is identified as one of the most promising anode materials, which has sparked a research boom. However, the intrinsically high reactivity triggers a repeating fracture/reconstruction process of the solid electrolyte interphase, side reactions with electrolyte and lithium dendrites, detrimental to the electrochemical performance of lithium metal batteries (LMBs). Even worse, when exposed to air, lithium metal will suffer severe atmospheric corrosion, especially the reaction with moisture, leading to grievous safety hazards. To settle these troubles, constructing air‐stable protective layers (ASPLs) is an effective solution. In this review, besides the necessity of ASPLs is highlighted, the modified design criteria, focusing on enhancing chemical/mechanical stability and controlling ion flux, are proposed. Correspondingly, current research progress is comprehensively summarized and discussed. Finally, the perspectives of developing applicable lithium metal anodes (LMAs) are put forward. This review guides the direction for the practical use of LMAs, further pushing the evolution of safe and stable LMBs. Abstract : In this review, besides the necessity of air‐stable protective layers (ASPLs) for the Li metal anode (LMA) is highlighted, the state‐of‐the‐art modified design criteria, focusing on enhancing chemical/mechanical stability and controlling ion flux, are proposed. Correspondingly, current research progress and strategies are comprehensively summarized and discussed. Finally, the perspectives of developing applicable LMA are put forward.